A Comprehensive Systematic Review on Effective Strategies for Student Engagement in Blended Learning Environments - Wibowo, Amin Ari (Journal of Blended and Technical Education, 2024)
Objective: This study aims to systematically review the empirical literature on blended learning, student engagement, and learning outcomes, particularly in the context of higher education in Indonesia, while also comparing global findings. By examining the effectiveness of blended learning designs in enhancing student engagement and learning outcomes, this research seeks to provide insights into how blended learning can be effectively applied to improve these aspects. Research Design & Methods: This study utilized Petticrew and Roberts' (2008) systematic review method to explore the impact of blended learning on student engagement and learning outcomes in higher education, focusing on relevant literature that met strict inclusion criteria and descriptive analysis based on four dimensions of learning outcomes. Findings: Blended learning increases student engagement across academic, behavioral, cognitive, and affective dimensions, In Indonesia, challenges such as unequal access to technology and the digital literacy gap still exist, but the benefits are equally distributed across STEM and non-STEM students. Implications & Recommendations: Blended learning design should consider equitable access to technology, digital skills training, and flexible approaches to overcome technical barriers and increase student engagement. Contribution & Value Added: This review synthesizes empirical findings to provide actionable insights into blended learning designs that balance technological innovation and accessibility. It highlights the universal applicability of blended learning across disciplines and its potential to transform higher education in Indonesia by addressing digital divides and fostering inclusive learning environments.